A new species of dendrochirotid holothuroid from deep water of southern Japan, with the erection of a new genus, Satsumaocnus (Echinodermata: Holothuroidea: Dendrochirotida: Cucumariidae: Colochirinae) - Yamana, Yusuke; Thandar, Ahmed S.; Hayashibara, Takeshi; Setiamarga, Davin H. E. (Zootaxa, 2022)
A new dendrochirotid sea cucumber, Satsumaocnus kaiyomarui gen. nov., sp. nov. from deep water of southern Japan is herein described. The new species displays the following unique characters : a cylindrical, soft body; mouth surrounded by five oral valves; 10 equal, dendritic tentacles arranged in a single circle, each composed of two tufts; a low, stout, compact, calcareous ring without posterior prolongations; body wall ossicles comprising an external layer of small, x-framed hourglass-shaped cups originally described as “double-faced x-framed cup ossicles” in a previous study reported by Yamana et al. (2019), and an inner layer of scarce dendriform/branched rods, sometimes taking the shape of delicate plate-like deposits. Although the general (external and internal) morphological characters of the new species correspond well with the characters of species within the cucumariid subfamily Colochirinae Panning, 1949, our material lacks any buttons or elaborate plate-like ossicles which characterize all extant genera within this subfamily. We, therefore, describe our material as a new species S. kaiyomarui sp. nov. within the new genus Satsumaocnus. The predominant body wall deposits of the new species strongly resemble the hourglass type ossicles of some species of the psolid genus Lissothuria (Verrill, 1867), but differ in their possession of a supporting x-shaped frame. In addition, it is noteworthy that these hourglass deposits also resemble the table ossicles of some holothuriids and stichopodids, when viewed from the side, especially the small tables of some Labidodemas and/or Stichopus species, while the dendriform rods resemble those of Thelenota.